Level of Acceptance of Telemedical Innovation and Its’ Correlation in Health Service At Medistra Hospital - Michael Aditya Marjoto; Hasyim; Endang Ruswanti (Alta Dharma Publisher, 2023)
Background: The development of telemedicine for patient care, especially during the COVID-19 pandemic, is essential to improve the quality of hospital services. Objective: The study aimed to examine whether the perception of innovation attribute factors simultaneously influences the level of acceptance of telemedicine in Medistra hospitals. Method: This study applied the cross-sectional design. The samples were all polyclinic nurses, outpatient admins, outpatient billing, and general practitioners at Medistra Hospital, totaling 120 respondents. Result: The transformational leadership style, career development, and commitment of health workers have a direct influence on performance of health workers. The results of the indirect effect indicate that the commitment of health workers is more dominant in mediating the impact of career development on the performance of health workers. Conclusion: The management unit needs to pay more attention to employee career development training to obtain a career path in the hospital by increasing their work. Recommendation: Further researchers need employee performance to expand the other factors work discipline factors, work culture, motivation, and others, using the broad population